Microbiological changes in the nests of leaf-cutting ants fed on sesame leaves - Pagnocca, F. C. [UNESP]; Carreiro, S. C. [UNESP]; Bueno, O. C. [UNESP]; Hebling, M. J. [UNESP]; Da Silva, O. A. [UNESP] (Wiley, 1996)
The number of bacteria and yeasts occurring in the organic matter inside the nests were determined both in colonies of leaf-cutting ants reared on Eucaliptus alba (control) or Sesamum indicum (experimental). Sesame leaves induce imbalance and nests usually die. In control nests the number of bacteria in newer sponge and in older sponge were similar (3.6 x 105 and 1.4 x 105 CFU/g, respectively) whereas in waste deposit the mean reached 7.3 x 107 CFU/g. The most Probable Number (MPN/g) of yeasts were 2.7 x 104, 1.3 x 105/g and 2.2 x 104 for newer sponge, older sponge and waste deposit, respectively. Using material from older sponge for comparison, the number of bacteria and yeasts reared on sesame leaves showed significant differences. The number of bacteria was 3.3 x 107 CFU/g, a value close to that found in waste deposit of normal (control) nests, whereas the number of yeasts was 6.7 x 105/g. These changes in microbial populations due to the effect of sesame leaf uptake could be a significant factor in nest imbalance and mortality when leaf-cutting ants are consuming toxic plants.
Keywords: Atta; Bacteria (microorganisms); Formicidae; Sesamum indicum